2008
DOI: 10.1021/ie0707974
|View full text |Cite
|
Sign up to set email alerts
|

Flue-Gas Carbon Capture on Carbonaceous Sorbents:  Toward a Low-Cost Multifunctional Carbon Filter for “Green” Energy Producers

Abstract: A low-pressure Carbon Filter Process (patent pending) is proposed to capture carbon dioxide (CO 2 ) from flue gas. This filter is filled with a low-cost carbonaceous sorbent, such as activated carbon or charcoal, which has a high affinity (and, hence, high capacity) to CO 2 but not to nitrogen (N 2 ). This, in turn, leads to a high CO 2 /N 2 selectivity, especially at low pressures. The Carbon Filter Process proposed in this work can recover at least 90% of flue-gas CO 2 of 90%+ purity at a fraction of the cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
137
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(146 citation statements)
references
References 44 publications
1
137
0
4
Order By: Relevance
“…For instance, the CO 2 heat of adsorption on zeolite is substantial enough to cause the rise of adsorption temperature as much as 50°C. Thus, it has been reported that the CO 2 heat of adsorption on zeolite is *10 times higher than that on activated carbon at the same temperature and pressure (Radosz et al 2008;Zhao et al 2012). Some of the studies revealed the same isosteric heat of CO 2 adsorption for MOPs and activated carbons, reflecting the structural similarities between the two adsorbent materials.…”
Section: Heat Of Co 2 Adsorption Of the Adsorbentsmentioning
confidence: 83%
“…For instance, the CO 2 heat of adsorption on zeolite is substantial enough to cause the rise of adsorption temperature as much as 50°C. Thus, it has been reported that the CO 2 heat of adsorption on zeolite is *10 times higher than that on activated carbon at the same temperature and pressure (Radosz et al 2008;Zhao et al 2012). Some of the studies revealed the same isosteric heat of CO 2 adsorption for MOPs and activated carbons, reflecting the structural similarities between the two adsorbent materials.…”
Section: Heat Of Co 2 Adsorption Of the Adsorbentsmentioning
confidence: 83%
“…Zeolite 13X is by far the adsorbent most extensively studied in CO 2 separation processes, due to its high selectivity to CO 2 [21]. However, several studies have also appeared in the literature dealing with activated carbons [4,22]. Activated carbons present important advantages over zeolites, such as hydrophobicity, significant lower cost, and lower energy requirements to carry out their regeneration (the isosteric heat of adsorption of CO 2 over activated carbons is ca.…”
Section: Introductionmentioning
confidence: 99%
“…Ho et al estimated that using zeolite 13X, a capture cost of US$ 51 per ton of CO 2 avoided could be attained, including the cost of product compression (purity of 48 %), with an additional capital investment for capture of US$ 1300 per kW [3]. Radosz et al estimated a total cost of compressed-pipeline ready CO 2 of US$ 27 per ton for a power plant integrated TSA process, and of US$ 44 per ton for a VSA process, using an activated carbon as adsorbent [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…+34 985 11 90 90; Fax: +34 985 29 76 62 e-mail address: frubiera@incar.csic.es regenerate the diluted amine solvent: a parasitic loss of 30% of the net power is expected from the use of MEA processes [3]. Adsorption is a separation technology with the potential to reduce the energy penalty of the capture step compared to amine scrubbing [4][5][6][7][8]. The main advantages of adsorption processes over amine scrubbing are the lower energy requirements and the higher capacity on a volume basis [9].…”
Section: Introductionmentioning
confidence: 99%